Trimethylamine QCM sensor and preparation method thereof and intelligent detection system

By constructing the WS2/PAA composite material as the gas-sensitive coating of QCM sensors, the problems of poor selectivity and incomplete recovery in the prior art are solved, and efficient and accurate detection of trimethylamine is achieved and excellent performance.

CN117268984BActive Publication Date: 2025-04-04CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311209525.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-04-04
Estimated Expiration
2043-09-19

AI Technical Summary

Technical Problem

Existing QCM sensors have poor selectivity and incomplete recycling when detecting trimethylamine, making it difficult to achieve efficient and accurate detection.

Method used

By constructing a WS2/PAA composite with layer-by-layer stacked nanosheet structures as a gas-sensitive coating, the unique structure of WS2 and the carboxy groups of PAA improve the sensitivity and selectivity of the sensor.

Benefits of technology

It realizes efficient and accurate detection of trimethylamine, and the sensor has high sensitivity, short response/recovery time, excellent selectivity, repeatability and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117268984B_ABST
    Figure CN117268984B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of gas sensors, and specifically relates to a trimethylamine QCM sensor, a preparation method thereof, and an intelligent detection system. The present invention prepares a WS2 / PAA composite material by a hydrothermal method and a solution polymerization method, and PAA nanoparticles are tightly attached to the surface of WS2 nanosheets stacked layer by layer. The trimethylamine QCM sensor constructed in this way exhibits excellent sensing performance for trimethylamine detection, including high sensitivity, short response / recovery time, and low detection limit, and has excellent selectivity, repeatability, and stability. At the same time, the intelligent detection system constructed based on the trimethylamine QCM sensor can achieve high-precision and ultra-fast detection of trimethylamine decomposed during food corruption, and then analyze and judge the freshness of food.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of QCM sensors, and in particular relates to a trimethylamine QCM sensor and a preparation method thereof, and an intelligent detection system. Background Art

[0002] Trimethylamine (TMA) is an organic amine compound with a pungent odor. It is mainly used as a disinfectant, natural gas alarm, analytical reagent and organic synthesis raw material. It is also used as a raw material for medicine, pesticides, photographic materials, rubber additives, explosives, chemical fiber solvents, surfactants and dyes. However, it is toxic and has a strong irritating effect on the human body. It is also flammable and explosive, and has the risk of combustion and explosion. At the same time, trimethylamine is also closely related to seafood. During the corruption of seafood, trimethylamine will be released, and the concentration released is positively proportional to the degree of corruption. Long-term consumption of rotten seafood will cause abdominal pain, diarrhea, nausea, vomiting, etc. In severe cases, it will cause shock and even cause death of the patient. Therefore, in order to reduce environmental pollution and protect human health, it is very necessary to effectively detect trace amounts of TMA in industrial production and living environments.

[0003] At present, the sensors used to detect TMA mainly include resistance sensors, photoelectric sensors, biosensors and quartz crystal microbalance (QCM) sensors. Although resistance sensors can achieve low detection limit detection, the detection power consumption is large; while photoelectric sensors and biosensors have the disadvantages of poor real-time performance and poor long-term stability respectively. In contrast, QCM sensors have attracted widespread attention due to their high sensitivity, fast response speed, low detection limit, low production cost, and room temperature detection. QCM sensors are based on the piezoelectric effect. After the sensing material adsorbs the gas to be measured, the concentration of the gas to be measured is indirectly reflected through the change of frequency, and has a detection accuracy of ng level.

[0004] Common sensing materials for QCM sensors include metal oxides, polymers, and transition metal sulfides (TMDs). Among them, transition metal sulfides (TMDs) have unique properties and functions due to their unique 2D structure, and have great application value as sensing materials. WS2, as a typical transition metal sulfide, has a high specific surface area and surface activity, a large lattice spacing, and fast electron transport properties. Its vertical stacking layers of covalently bonded WS atoms allow the target gas to diffuse freely, and hydrogen bonds and weak van der Waals forces improve the reversibility and accuracy of detection at room temperature. These advantages give WS2 great potential, making it the preferred material among TMDs. However, as a single sensitive material, WS2 has disadvantages such as incomplete recovery and poor selectivity. However, studies have shown that compared with single materials, WS2 / MWCNTs nanocomposites show lower detection limits, faster response times, higher gas-sensitive responses, and better selectivity and stability when detecting TMA; compared with single materials, the detection limit (LOD) of nanoflower-like WO3 / WS2 composites when detecting NO2 is ≤5ppb, and they show better selectivity, reproducibility, and long-term stability for NO2. Therefore, the gas-sensing performance of QCM sensors can be improved by constructing composite materials as sensing layers. The combination of composite materials can not only retain the original advantages and complement the disadvantages, but also produce new performance through synergy. Summary of the invention

[0005] The present invention provides a trimethylamine QCM sensor and a preparation method thereof and an intelligent detection system. The present invention overcomes the disadvantages of WS2 as a single sensitive material, such as poor selectivity, by constructing a WS2 / PAA composite material with a layer-by-layer stacked nanosheet structure. As a gas-sensitive material of a QCM sensor, the WS2 / PAA composite material has high sensitivity, short response / recovery time, and excellent performances of good selectivity, repeatability and stability, and can realize efficient and accurate detection of trimethylamine.

[0006] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a trimethylamine QCM sensor, comprising a gas-sensitive coating and a substrate, wherein the gas-sensitive coating is coated on the surface of the substrate with a coating thickness of 0.1-0.2 mm, the gas-sensitive coating is a WS2 / PAA composite material, and the substrate is a quartz crystal microbalance wafer.

[0007] Specifically, polyacrylic acid (PAA), as an organic acid, carries a large number of carboxyl groups, which can interact with the groups on the surface of WS2, improve the solubility of WS2 in the solvent, increase the density of the composite material, and can also effectively interact with alkaline target molecules through reversible Lewis acid-base intermolecular reactions. Compared with sensors made of a single material, the synergistic effect of the two enhances the sensing properties of the WS2 / PAA composite sensor.

[0008] Furthermore, in the WS2 / PAA composite material, PAA nanoparticles are tightly attached to the surface of WS2 nanosheets stacked layer by layer, and the diameter of the WS2 nanosheets is 600-800nm ​​and the thickness is 5-7nm. The detection limit of the sensor is 20ppb, the sensitivity is 107.43Hz / ppm, and the response / recovery time is 27s / 33s.

[0009] A second aspect of the present invention provides a method for preparing the above trimethylamine QCM sensor, the method comprising:

[0010] (1) Dissolve thioacetamide and WCl6 in deionized water and obtain WS2 through hydrothermal reaction;

[0011] (2) Add acrylic acid and ammonium persulfate into deionized water, mix well, add isopropanol and perform reflux polymerization to obtain PAA buffer solution;

[0012] (3) Mix WS2 and PAA buffer and stir the mixture at room temperature to obtain a WS2 / PAA composite material;

[0013] (4) The WS2 / PAA composite material is dispersed in an anhydrous ethanol solution to obtain a dispersion, which is then evenly coated on a substrate surface, and dried to obtain the trimethylamine QCM sensor.

[0014] Furthermore, in the step (1), the addition ratio of thioacetamide to WCl6 is (3.9-4.5 g): (1.9-2.3 g), the reaction temperature is 200-300°C, and the reaction time is 20-28 h.

[0015] Furthermore, in the step (2), the addition ratio of acrylic acid, ammonium persulfate and isopropanol is (3.2-3.8 g): (0.7-0.9 g): (0.25-0.35 g), the reflux polymerization temperature is 55-85° C., and the reflux polymerization time is 8-16 h.

[0016] Furthermore, the reaction time in step (3) is 2-6 hours, and the mass ratio of WS2:PAA in the WS2 / PAA composite material is 1:(2-4).

[0017] Furthermore, the concentration of the dispersion in step (4) is 0.004-0.008 g / mL.

[0018] The third aspect of the present invention provides an application of the trimethylamine QCM sensor in food freshness detection, especially seafood freshness detection.

[0019] A fourth aspect of the present invention provides an intelligent detection system, including a sealed air chamber, a QCM sensor, a QCM tester, an analysis module, and a terminal;

[0020] The QCM sensor is the aforementioned trimethylamine QCM sensor, which is located inside the closed gas chamber and is used to detect trimethylamine gas in real time to obtain a gas concentration signal and convert the gas concentration signal into a frequency shift signal;

[0021] The QCM tester is connected to the QCM sensor and is used to collect the frequency shift signal output by the QCM sensor in real time;

[0022] The analysis module is loaded on the terminal, and is used to analyze and process the frequency shift signal acquired by the QCM tester, and output the concentration of trimethylamine based on the analysis and processing result to determine the freshness of the food; the terminal is connected to the QCM tester, and is used to display the food freshness result.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention prepares WS2 / PAA composite materials by hydrothermal method and solution polymerization method. PAA nanoparticles are tightly attached to the surface of WS2 nanosheets stacked layer by layer. The three-dimensional structure with large specific surface area increases the adsorption sites of target molecules. At the same time, the prepared material has rich functional groups, which effectively enhances the synergistic effect of the sensing material and the interaction with the target molecules.

[0025] (2) The trimethylamine QCM sensor of the present invention has high sensitivity, short response / recovery time, low detection limit, and excellent selectivity, repeatability and stability. The intelligent detection system constructed with this sensor can achieve high-precision and ultra-fast detection of trimethylamine decomposed during food spoilage, and then analyze and judge the freshness of food. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The figure is a process flow chart of the manufacturing process of the trimethylamine QCM sensor of the present invention;

[0027] Figure 2 This is a test flow chart of the trimethylamine QCM sensor of the present invention;

[0028] Figure 3 a is a SEM image of the WS2 / PAA composite material in Example 1 at 1350X magnification; Figure 3 b is a SEM image of the WS2 / PAA composite material in Example 1 at 1600X magnification; Figure 3 c is the SEM image of WS2 in Example 1 at 60000X magnification; Figure 3 d is the SEM image of WS2 in Example 1 at 135000X magnification;

[0029] Figure 4a is the XRD pattern of WS2, PAA and WS2 / PAA composite material in Example 1; Figure 4 b is the FT-IR spectra of WS2, PAA and WS2 / PAA composite materials in Example 1;

[0030] Figure 5 a is a TEM image of the WS2 / PAA composite material in Example 1 at 450000X magnification; Figure 5 b is the TEM image of WS2 in Example 1 at 2250000X magnification; Figure 5 c is the HRTEM image of WS2 in Example 1 at 7000000X magnification; Figure 5 d is the HRTEM image of WS2 in Example 1 at 7000000X magnification;

[0031] Figure 6 a is the XPS spectrum of WS2 / PAA composite material; Figure 6 b is the XPS spectrum of W 2f; Figure 6 c is the XPS spectrum of S 2p; Figure 6 d is the XPS spectrum of C 1s;

[0032] Figure 7 a is the gas-sensing response of Examples 1, 4-5 and Comparative Examples 1-3 at different PAA concentrations; Figure 7 b is the dynamic response curve of Example 1 and Comparative Examples 1-2 at different PAA concentrations; Figure 7 c is the fitting curve of Example 1 and Comparative Examples 1-2 at different PAA concentrations; Figure 7 d is the linear fitting curve of Example 1 and Comparative Examples 1-2 at low PAA concentration;

[0033] Figure 8 a is a response / recovery time curve of Example 1 and Comparative Examples 1-2 at a trimethylamine concentration of 1 ppm; Figure 8 b is the continuous cycle test curve of Example 1 at different trimethylamine concentrations; Figure 8 c is the cyclic repeatability test curve diagram of Example 1; Figure 8 d is a long-term stability test curve of Example 1 in different concentrations of trimethylamine environments within 30 days;

[0034] Fig. 9 a is the response curve of Example 1 to 500 ppb trimethylamine at 25°C and different relative humidity; Fig. 9 b is a gas selectivity test diagram of Example 1 and Comparative Examples 1-2;

[0035] Fig.10 a is the conductivity spectrum of the sensor of Comparative Example 1 at different trimethylamine concentrations; Fig.10b is the conductivity spectrum of the sensor of Comparative Example 2 at different trimethylamine concentrations; Fig.10 c is the conductivity spectrum of the sensor of Example 1 at different trimethylamine concentrations; Fig.10 d is a graph showing the change in quality factor of the sensor of Example 1 and Comparative Examples 1-2 at different trimethylamine concentrations;

[0036] Fig.11 It is the interaction reaction diagram between molecules of the WS2 / PAA composite material of the present invention;

[0037] Fig.12 Schematic diagram of the adsorption mechanism of trimethylamine on the WS2 / PAA composite material of the present invention;

[0038] Fig.13 a is the response diagram of the sensor of Example 1 to the TMA concentration during the 24-hour decay of fresh shrimp; Fig.13 b is the response diagram of the sensor of Example 1 to the TMA concentration during the 24-hour decay of fresh fish;

[0039] Fig.14 a is the analysis result of fresh food; Fig.14 b is the analysis result of food that is about to go bad; Fig.14 c is the analysis result of spoiled food. DETAILED DESCRIPTION

[0040] The principles and features of the present invention are described below in conjunction with examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.

[0041] Isopropyl alcohol (C3H8O, 99.7%), ammonium persulfate [APS, (NH4)2S2O8, 99%] and ethanol (C2H6O, 99%) were analytical reagents purchased from Sinopharm Chemical Reagent Co., Ltd. Tungsten chloride (WCl6, 99.9%) was provided by Aladdin Reagent Co., Ltd. (Shanghai, China). Thioacetamide (TAA, C2H5NS, 99%) and acrylic acid (CH2=CHCOOH, 99%) were provided by Shanghai MacLean Biochemical Technology Co., Ltd.

[0042] Figure 1 The following is a flow chart of the manufacturing process of the trimethylamine QCM sensor of the present invention. Figure 2 This is a test flow chart of the trimethylamine QCM sensor of the present invention.

[0043] Example 1

[0044] A trimethylamine QCM sensor mainly consists of a gas-sensitive coating and a quartz crystal microbalance chip. The gas-sensitive coating is coated on the surface of a silver electrode of the quartz crystal microbalance chip with a coating thickness of 0.12 mm. The gas-sensitive coating is a WS2 / PAA composite material.

[0045] The preparation method comprises the following steps:

[0046] S1. Dissolve 3.9 g of TAA powder in 75 mL of deionized water and make it into a transparent uniform solution by ultrasound. Then quickly add 1.9 g of WCl6 powder to the solution and stir it magnetically for 15 minutes to form a mixed solution. Then transfer the mixed solution to 100 mL of para-polyphenol liner (PPL) and slowly raise the temperature from room temperature to 200 °C. o C, and at 200 o The hydrothermal reaction was continued for 20 hours at 60 °C. After the reactor was cooled to room temperature, the resulting black solution was centrifuged and washed three times with deionized water and ethanol respectively. o C in a vacuum oven overnight to obtain WS2.

[0047] S2. 3.2 g of acrylic acid and 0.7 g of ammonium persulfate were added to 10 mL of deionized water while magnetic stirring. After stirring for 20 minutes, the solution was transferred to a three-necked flask. Subsequently, 0.25 g of isopropanol was added and the mixture was heated at 55 o C for 8 hours to obtain PAA buffer.

[0048] S3. 0.2 g of WS2 sample was added to 0.4 g of PAA buffer solution and stirred vigorously at room temperature for 2 h. After complete reaction, WS2 / PAA composite material (WS2:PAA (质量比) =1:2).

[0049] S4. 0.04 g of WS2 / PAA composite material was evenly dispersed in 10 mL of anhydrous ethanol solution, and then evenly coated on the surface of the silver electrode of the quartz crystal microbalance chip by spin coating, and dried at room temperature to obtain the trimethylamine QCM sensor.

[0050] The SEM images of WS2 and WS2 / PAA composite materials prepared in Example 1 are as follows: Figure 3 As shown, Figure 3 (ab) are WS2 / PAA composite materials, and 3 (cd) are WS2. It can be seen from the characterization images that the WS2 is a nanosheet structure stacked layer by layer. The edges of the WS2 nanosheets stacked layer by layer according to a certain amount form a clear petal shape. The PAA nanoparticles are tightly attached to the surface of the WS2 nanosheets stacked layer by layer to form a WS2 / PAA composite material. The three-dimensional structure with a large specific surface area increases the adsorption sites of the target molecules. The thickness of the nanosheet is about 5nm, and the diameter of the WS2 nanosheet is 600nm.

[0051] Figure 4a shows the XRD characterization results of WS2, PAA and WS2 / PAA composites. The scanning results show that the 2θ diffraction peaks of the prepared WS2 appear at 14.32°, 29.12°, 32.08°, 42.98°, 48.56° and 57.06°, corresponding to the (002), (004), (100), (006), (105) and (110) crystal planes of the WS2 phase, respectively, confirming the hexagonal structure of WS2, and the broadening and movement of the diffraction peaks may be due to the stacking of WS2 nanosheets. PAA has no obvious characteristic peaks, only at 15 o -30 o In the XRD spectrum of WS2 / PAA composite material, in addition to the diffraction peak of WS2 nanosheets, the material sample has a broad diffraction peak in the range of 20 o -30 o The diffraction peak at the range is also raised, which may be the effect of the broad diffraction peak of PAA. The above results confirm the successful synthesis of WS2 / PAA composite materials. Figure 4 b is the FT-IR characterization results of WS2, PAA and WS2 / PAA composites. The prepared WS2 has the following peaks at 3435 and 1618 cm -1 The characteristic peak at 3142 cm corresponds to the stretching vibration and bending vibration of -OH. -1 The characteristic peaks correspond to the stretching vibration of -NH2, 1385, 620cm -1 The characteristic peak at 2553 cm corresponds to the symmetric stretching vibration of -COOH and W−S bonds, indicating that the prepared WS2 contains -NH2, -OH and -COOH. -1 The characteristic peak at 1718 cm -1 The characteristic peak at 1244 cm -1 The characteristic peak corresponds to the stretching vibration of CO, 943 cm -1 The characteristic peak at 812 cm corresponds to the absorption bend of the bonding -OH, -1 The characteristic peak at corresponds to the in-plane swing of the bonded -CH3. From the spectrum of the WS2 / PAA composite material, it can be seen that the peaks in the single materials WS2 and PAA can be well reproduced, indicating the successful synthesis of the material.

[0052] according to Figure 5 (ab) It can be seen that the results of its characterization are consistent with the results of SEM characterization. In particular, Figure 5 It can be seen in c that the edges of the stacked and staggered WS2 nanosheets present an irregular structure. At the same time, the lattice fringe spacing of WS2 is 0.31 and 0.62 nm, which belong to the (004) and (002) crystal planes of WS2, respectively, which is consistent with the characterization results of XRD.

[0053] The elemental composition and chemical state of the composite materials were analyzed by XPS. Figure 6 Characterization results of WS2 / PAA. Figure 6 a Prove that the main elements are W, S, C and O. Figure 6 The W 4f is shown in the measured spectrum of W in b. 5 / 2 and W 4f 7 / 2 The two strong signals of 31.9 and 34.1 eV are respectively attributed to W 4+ 4f 7 / 2 and 4f 5 / 2 ; The two peaks at 35.8 and 38.1 eV are respectively attributed to W 6+ 4f 7 / 2 and 4f 5 / 2 This is because during the material preparation process, WS2 is partially oxidized to produce W 6+ .exist Figure 6 In the measured spectrum of c S, the two characteristic peaks centered at 161.5 and 162.7 eV are respectively attributed to S 2− 2p 3 / 2 and S 2− 2p 1 / 2 The characteristic peak centered at 163.8 eV is attributed to the SC bond formed by the residual sulfur during the material preparation process. Figure 6 In the measured spectrum of d C, the characteristic peaks centered at 284.7, 286.1, and 288.7 eV are attributed to the C-C bond, C-O bond, and C=O bond in PAA, respectively.

[0054] Example 2

[0055] A trimethylamine QCM sensor is mainly composed of a gas-sensitive coating and a quartz crystal microbalance chip. The gas-sensitive coating is coated on the silver electrode surface of the quartz crystal microbalance chip, and the coating thickness is 0.15 mm. The gas-sensitive coating is a WS2 / PAA composite material. The WS2 / PAA composite material is PAA nanoparticles tightly attached to the surface of WS2 nanosheets stacked layer by layer. The diameter of the WS2 nanosheet is 700 nm and the thickness is 6 nm.

[0056] The preparation method comprises the following steps:

[0057] S1. Dissolve 4.2 g of TAA powder in 75 mL of deionized water and make it into a transparent uniform solution by ultrasound. Then quickly add 2.1 g of WCl6 powder to the solution and stir it magnetically for 15 minutes to form a mixed solution. Then transfer the mixed solution to 100 mL of para-polyphenol liner (PPL) and slowly heat the temperature from room temperature to 250 °C. o C, and at 250 oThe hydrothermal reaction was continued for 24 hours at 60 °C. After the reactor was cooled to room temperature, the resulting black solution was centrifuged and washed three times with deionized water and ethanol respectively. o C in a vacuum oven overnight to obtain WS2.

[0058] S2. 3.5 g of acrylic acid and 0.8 g of ammonium persulfate were added to 10 mL of deionized water while magnetic stirring. After stirring for 20 minutes, the solution was transferred to a three-necked flask. Subsequently, 0.3 g of isopropanol was added and heated at 70 o C for 12 hours to obtain PAA buffer.

[0059] S3. 0.2 g of WS2 sample was added to 0.6 g of PAA buffer solution and stirred vigorously at room temperature for 4 h. After complete reaction, WS2 / PAA composite material (WS2:PAA (质量比) =1:3).

[0060] S4. 0.06 g of WS2 / PAA composite material was evenly dispersed in 10 mL of anhydrous ethanol solution, and then evenly coated on the silver electrode surface of a quartz crystal microbalance chip by spin coating, and dried at room temperature to obtain the trimethylamine QCM sensor.

[0061] Example 3

[0062] A trimethylamine QCM sensor is mainly composed of a gas-sensitive coating and a quartz crystal microbalance chip. The gas-sensitive coating is coated on the silver electrode surface of the quartz crystal microbalance chip, and the coating thickness is 0.18 mm. The gas-sensitive coating is a WS2 / PAA composite material. The WS2 / PAA composite material is PAA nanoparticles tightly attached to the surface of WS2 nanosheets stacked layer by layer. The WS2 nanosheets have a diameter of 800 nm and a thickness of 7 nm.

[0063] The preparation method comprises the following steps:

[0064] S1. Dissolve 4.5 g of TAA powder in 75 mL of deionized water and make it into a transparent uniform solution by ultrasound. Then quickly add 2.3 g of WCl6 powder to the solution and stir it magnetically for 15 minutes to form a mixed solution. Then transfer the mixed solution to 100 mL of para-polyphenol liner (PPL) and slowly raise the temperature from room temperature to 300 °C. o C, and at 300 o The hydrothermal reaction was continued for 28 hours at 60 °C. After the reactor was cooled to room temperature, the resulting black solution was centrifuged and washed three times with deionized water and ethanol respectively. o C in a vacuum oven overnight to obtain WS2.

[0065] S2. 3.8 g of acrylic acid and 0.9 g of ammonium persulfate were added to 10 mL of deionized water while magnetic stirring. After stirring for 20 minutes, the solution was transferred to a three-necked flask. Subsequently, 0.35 g of isopropanol was added and heated at 85 o C for 16 hours to obtain PAA buffer.

[0066] S3. 0.2 g of WS2 sample was added to 0.8 g of PAA buffer solution and stirred vigorously at room temperature for 6 h. After complete reaction, WS2 / PAA composite material (WS2:PAA (质量比) =1:4).

[0067] S4. 0.08 g of WS2 / PAA composite material was evenly dispersed in 10 mL of anhydrous ethanol solution, and then evenly coated on the surface of the silver electrode of the quartz crystal microbalance chip by spin coating, and dried at room temperature to obtain the trimethylamine QCM sensor.

[0068] Example 4

[0069] Refer to Example 1, the difference is that the mass ratio of WS2:PAA in the gas-sensitive coating WS2 / PAA composite material is 1:3.

[0070] Example 5

[0071] Refer to Example 1, the difference is that the mass ratio of WS2:PAA in the gas-sensitive coating WS2 / PAA composite material is 1:4.

[0072] Comparative Example 1

[0073] Refer to Example 1, except that the gas-sensitive coating is WS2.

[0074] Comparative Example 2

[0075] Refer to Example 1, except that the gas-sensitive coating is PAA.

[0076] Comparative Example 3

[0077] Refer to Example 1, the difference is that the mass ratio of WS2:PAA in the gas-sensitive coating WS2 / PAA composite material is 1:1.

[0078] Trimethylamine sensor performance test

[0079] like Figure 2 As shown in the figure, the gas-sensing performance test uses air as the background and is carried out at a temperature of 25 oC, in a closed air chamber with a humidity of 33% RH. Different volumes of target gas were injected into the air chamber through a syringe, and the real-time frequency shift signal of the QCM sensor was recorded by a QCM tester (including an electrochemical workstation CHI 440c and an oscillator), and the admittance spectrum of the QCM sensor was collected by a vector network analyzer (Keysight ENAE5063A).

[0080] The frequency shift of six QCM sensors coated with WS2 (Comparative Example 1), PAA (Comparative Example 2) and WS2 / PAA composites with different WS2:PAA mass ratios (Examples 1, 4-5 and Comparative Example 3) in different concentrations of TMA gas was tested. Figure 7 As shown in a, despite the different mass ratios of WS2 / PAA, the frequency shift of the WS2 / PAA composite QCM sensor is always higher than that of pure WS2 and pure PAA sensors at the corresponding TMA concentrations. As the PAA content increases, the frequency shift of the WS2 / PAA composite QCM sensor first increases and then decreases in the corresponding concentration of TMA, and reaches the best frequency shift response when the WS2:PAA (mass ratio) is 1:2.

[0081] The dynamic step frequency shift responses of the three sensors WS2 (Comparative Example 1), PAA (Comparative Example 2) and WS2 / PAA (Example 1) at different concentrations were further tested. The test interval was 100s and the test temperature was 25 o C. As Figure 7 As shown in Figure b (WS2, PAA, WS2 / PAA from top to bottom), the detection limits of the three sensors are as low as 20ppb, and all three show a greater frequency shift response with the increase of TMA concentration. After leaving the TMA environment, they can all be well restored to the baseline level. Among them, in the TMA environment of 0.02, 0.05, 0.1, 0.5, 1, 5 and 10ppm, the WS2 / PAA composite material sensor shows the best gas-sensitive response, and the corresponding frequency shifts are 31.01, 41.66, 71.75, 105.98, 144.92, 173.61 and 227.57Hz respectively.

[0082] Figure 7 c is the fitting curve of the dynamic step frequency shift response of the WS2 (Comparative Example 1), PAA (Comparative Example 2) and WS2 / PAA (Example 1) coating sensors. The fitting equations corresponding to the three sensors are Y=-60.06X 0.32 ,Y=-75.89X 0.30 and Y=-122.49X 0.27 , correlation coefficient (R 2 ) are 0.97258, 0.98711 and 0.9583. Figure 7d is the linear fitting curve of pure WS2 (Comparative Example 1), pure PAA (Comparative Example 2) and WS2 / PAA composite material (Example 1) sensors at lower concentrations. It can be concluded that the sensitivities of the three sensors are 53.42, 64.66 and 107.43 Hz / ppm, respectively. The synergistic effect of WS2 and PAA greatly improves the sensitivity of the WS2 / PAA composite material sensor.

[0083] The response / recovery time will affect the real-time monitoring effect of the sensor. Therefore, the response / recovery time of three sensors in a 1ppmTMA environment was tested. Figure 8 As shown in a, compared with 42s / 38s of the pure WS2 sensor (Comparative Example 1) and 30s / 45s of the pure PAA sensor (Comparative Example 2), the WS2 / PAA composite material sensor (Example 1) has a faster response / recovery time, which can reach 27s and 33s, respectively. Figure 8 b The continuous cycle curve of the WS2 / PAA composite sensor to different concentrations of TMA in Example 1 was tested. As the TMA concentration in the gas chamber increases, the frequency shift response of the sensor changes according to the established rules. When the TMA concentration decreases, the sensor can also recover to the relative baseline value relatively smoothly, showing excellent hysteresis characteristics.

[0084] During repeated use, whether the response / recovery time and frequency shift can be consistent is an important indicator for evaluating whether the sensor repeatability is good. o Under room temperature of 1.5 °C, the WS2 / PAA sensor in Example 1 was tested for repeatability at 50 ppb, 500 ppb and 5 ppm trimethylamine concentrations. The sensor was immersed in the trimethylamine environment and air for 100 s, and the measurement was repeated three times at each concentration. The trimethylamine concentration in the air chamber increased from low to high. Figure 8 c, under repeated tests of the same gas concentration, the frequency shift and response / recovery time of the sensor are consistent. The frequency shift of the sensor at different concentrations in the repeatability test is also consistent with the dynamic step frequency shift response, which has excellent repeatability. The frequency shift response, i.e., long-term stability, of the WS2 / PAA sensor (Example 1) at 50ppb, 500ppb, and 5ppm trimethylamine concentrations was tested within 30 days, with one group tested every five days. The test results are shown in Figure 3. Figure 8 d. The results show that during the test period, the frequency shift response of the sensor at each concentration did not fluctuate significantly, and it has good long-term stability.

[0085] In 25 o At room temperature, when the relative humidity in the air chamber changes from 11% to 97%, the frequency shift response of the WS2 / PAA sensor in a 500 ppb trimethylamine environment is tested. Fig. 9 As shown in a. As the relative humidity in the air chamber increases, the frequency shift of the sensor increases from 88.68Hz at 11%RH to 174.76Hz at 97%RH. This is due to the adsorption of water molecules in the environment by the hydrophilic groups of the WS2 / PAA sensing coating. Therefore, in the actual use of the WS2 / PAA sensor, in order to ensure the authenticity of the gas concentration test, the humidity compensation method can be considered to improve the accuracy of the results. In addition, in the actual use process, it is also a huge challenge to overcome the frequency shift of the sensor caused by the adsorption of non-target gases. To this end, at a temperature of 25 o C. In an air chamber with a relative humidity of 33% RH, the frequency shift response of the sensors in Example 1 and Comparative Examples 1-2 in an environment with a concentration of 1 ppm of trimethylamine, aniline, xylene, acetone, dimethylacetamide, ammonia and hydrogen sulfide was tested. Fig. 9 b The test results show that compared with the other six non-target gases, the three sensors all exhibited good affinity for trimethylamine and had good specificity, but the sensor in Example 1 showed better gas selectivity than pure WS2 and pure PAA sensors.

[0086] The resonance characteristics of the pure WS2 sensor (Comparative Example 1), the pure PAA sensor (Comparative Example 2) and the WS2 / PAA composite trimethylamine sensor (Example 1) can be analyzed by the admittance spectrum and the quality factor. Fig.10 (ac) is 25 o Conductivity spectra of the three sensors at 0, 0.02, 0.05, 0.1, 0.5, 1, 5 and 10 ppm trimethylamine concentrations measured at room temperature. Fig.10 d is the quality factor of the three sensors at the corresponding gas concentration calculated from the conductivity spectrum. As the concentration of trimethylamine increases, the adsorption capacity of the sensor increases, so the central peak moves to a lower frequency, and the corresponding central frequency is consistent with the above test; at the same time, the central peak of the sensor decreases and the half-bandwidth becomes wider. This is because the adsorption of the gas to be tested by the sensor causes the viscosity of the gas-sensitive coating to increase. The recognition process is also accompanied by energy loss, so the quality factor also decreases. From Fig.11 It can also be seen that the introduction of WS2 nanosheets can support PAA. The synergistic effect of the two reduces the energy consumption of WS2 / PAA composite materials, enhances mechanical stability, and achieves the best quality factor.

[0087] Explanation of the performance mechanism of trimethylamine QCM sensor

[0088] Schematic diagram of gas sensing mechanism Fig.12As shown. WS2 is a two-dimensional transition metal sulfide. Its mesoporous properties and nanosheet shape increase the specific surface area and active exposure points of the sensing film. The vertical stacking layers of covalently bonded WS atoms promote the diffusion, penetration and adsorption of TMA gas. WS2 is a p-type semiconductor. The band gap of PAA is narrow. When WS2 and PAA are combined into a composite material, the single electron pair on the N atom in TMA will be transferred to the composite material. WS2 prepared by hydrothermal method has functional groups such as amino, hydroxyl and carboxyl groups. These functional groups can interact with TMA molecules to form hydrogen bonds and weak van der Waals forces. The hydrogen bonds and van der Waals forces are weak and are destroyed in the air, so that TMA molecules are desorbed from the composite material, which provides a guarantee for the reversibility of detection at room temperature. In addition, TMA molecules are a Lewis base with a large number of carboxyl groups. They can not only react with the hydroxyl and amino groups on WS2 to form new lipid and amide bonds, improve the solubility of WS2, but also have reversible Lewis interactions with alkaline target gas molecules.

[0089] Food freshness testing

[0090] An intelligent detection system was constructed using the trimethylamine QCM sensor prepared in Example 1 to determine the freshness of food.

[0091] The intelligent detection system includes a closed gas chamber, a QCM sensor, a QCM tester, an analysis module and a terminal; the QCM sensor is located inside the closed gas chamber, and is used to detect trimethylamine gas in real time to obtain a gas concentration signal, and convert the gas concentration signal into a frequency shift signal; the QCM tester is connected to the QCM sensor, and is used to collect the frequency shift signal output by the QCM sensor in real time; the analysis module is loaded on the terminal, and is used to analyze and process the frequency shift signal collected by the QCM tester, and output the trimethylamine concentration based on the analysis and processing results to determine the freshness of the food; the terminal is connected to the QCM tester, and is used to display the food freshness results.

[0092] Fig.13 It is on 25 o C. Experimental test diagram for verifying the practicality of the prepared WS2 / PAA composite sensor at 33% RH, defining the concentration of trimethylamine volatilized from 100 grams of seafood as fresh, about to rot, and already rotten when it is 0-1ppm, 1-5ppm, and greater than 5ppm. It can be seen from the figure that 100 grams of shrimp and fish can maintain good freshness within the first 8 hours and the first 10 hours, respectively, which is the best edible stage. After 16 hours, the trimethylamine concentration will reach 5ppm, indicating that the shrimp and fish have rotted and cannot be eaten.

[0093] After collecting data using the WS2 / PAA composite sensor, a user-side analysis module was developed using MATLAB to determine the freshness of food. The analysis module has functions such as data import and result analysis. After the user imports the test data, the interface can display the frequency shift value and output the concentration of trimethylamine according to the fitting function, and then display the freshness of the food through the terminal. The three freshness levels of fresh, about to spoil, and already spoiled correspond to green, yellow, and red lights respectively. Fig.14 It is the food freshness rating interface. Fig.14 14a, 14b and 14c show the judgment results of fresh, about to spoil and spoiled food respectively.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. Trimethylamine QCM sensor, characterized in that, It comprises a gas-sensitive coating and a substrate, wherein the gas-sensitive coating is coated on the surface of the substrate with a coating thickness of 0.1-0.2 mm, the gas-sensitive coating is a WS2 / PAA composite material, and the substrate is a quartz crystal microbalance wafer; In the WS2 / PAA composite material, PAA nanoparticles are tightly attached to the surface of WS2 nanosheets stacked layer by layer, and the diameter of the WS2 nanosheets is 600-800nm ​​and the thickness is 5-7nm.

2. The trimethylamine QCM sensor according to claim 1, characterized in that: The sensor has a detection limit of 20 ppb, a sensitivity of 107.43 Hz / ppm, and a response / recovery time of 27 s / 33 s.

3. The method for preparing a trimethylamine QCM sensor according to any one of claims 1 to 2, characterized in that: The method comprises: (1) Dissolve thioacetamide and WCl6 in deionized water and obtain WS2 through hydrothermal reaction; (2) Add acrylic acid and ammonium persulfate into deionized water, mix well, add isopropanol and perform reflux polymerization to obtain PAA buffer solution; (3) Mix WS2 and PAA buffer and stir the mixture at room temperature to obtain a WS2 / PAA composite material; (4) The WS2 / PAA composite material is dispersed in an anhydrous ethanol solution to obtain a dispersion, which is then evenly coated on a substrate surface, and dried to obtain the trimethylamine QCM sensor.

4. The preparation method according to claim 3, characterized in that: In the step (1), the addition ratio of thioacetamide to WCl6 is (3.9-4.5 g): (1.9-2.3 g), the reaction temperature is 200-300°C, and the reaction time is 20-28 h.

5. The preparation method according to claim 3, characterized in that: In the step (2), the addition ratio of acrylic acid, ammonium persulfate and isopropanol is (3.2-3.8 g): (0.7-0.9 g): (0.25-0.35 g), the reflux polymerization temperature is 55-85° C., and the reflux polymerization time is 8-16 h.

6. The preparation method according to claim 3, characterized in that: The reaction time in step (3) is 2-6 hours, and the mass ratio of WS2:PAA in the WS2 / PAA composite material is 1:(2-4).

7. The preparation method according to claim 3, characterized in that: The concentration of the dispersion in step (4) is 0.004-0.008 g / mL.

8. Use of the trimethylamine QCM sensor according to any one of claims 1 to 2 in detecting food freshness.

9. An intelligent detection system, characterized in that: It includes a sealed gas chamber, a QCM sensor, a QCM tester, an analysis module and a terminal; The QCM sensor is the trimethylamine QCM sensor as claimed in any one of claims 1 to 2, located inside the closed gas chamber, and used for real-time detection of trimethylamine gas to obtain a gas concentration signal, and converting the gas concentration signal into a frequency shift signal; The QCM tester is connected to the QCM sensor and is used to collect the frequency shift signal output by the QCM sensor in real time; The analysis module is loaded on the terminal, and is used to analyze and process the frequency shift signal acquired by the QCM tester, and output the concentration of trimethylamine based on the analysis and processing result to determine the freshness of the food; the terminal is connected to the QCM tester, and is used to display the food freshness result.